[PP.02.23] NATURAL ANTIOXIDANT ICE-CREAM ACUTELY REDUCES BLOOD PRESSURE AND IMPROVES VASCULAR FUNCTION IN PATIENTS WITH METABOLIC SYNDROME. (September 2017) - Sanguigni, V.; Francomano, F.; Sorge, R.; Gnessi, L.
Abstract : Objective: Epidemiological investigations revealed an inverse correlation between the intake of polyphenols-containing foods and coronary artery disease mortality. A large number of studies has investigated the possible blood pressure (BP) lowering effect of different dietary supplements. We hypothesized that a natural antioxidant ice cream, product with a selected blend of cocoa, hazelnut and other ingredients from organic farming, could improve vascular function and decrease blood pressure in sample of patients with metabolic syndrome via an oxidative stress-mediated mechanism. Design and method: We performed a single blind crossover study in which we measured the acute effect of natural antioxidant ice cream, on vascular function and blood pressure in a population of patient with metabolic syndrome. 10 subjects (5 male, 5 female), mean age 56 years, were randomly allocated to a treatment sequence with 100 mg of antioxidant ice cream or milk ice cream in a cross-over, single-blind design. Total polyphenol content (mg/100 g) was significantly higher in antioxidant ice cream compared to milk ice cream (control (1817 vs 96). There was at least 1 week washout between the 2 phases of the study. Oxidative stress (assessed by measuring plasma hydroperoxides, analytic method dROMs), Nitric oxide (NO) bioavailability (NOx), vascular function (flow mediated dilatation, FMD) and blood pressure were assessed at baseline, after a 24 hours abstinence from food rich in polyphenols, and 2 hours after ingestion of ice cream. Results: Serum polyphenols (139, 28 ± 28, 32 vs 288, 57 ± 58, 12. p < 0.001), NOx (23, 34 ± 5, 24 vs 48, 24 ± 8, 66 .p < 0.001), FMD (2, 34 ± 1, 46 vs 6, 43 ± 1, 86 .p < 0.001) increased significantly, oxidative stress (D-Roms 426, 27 ± 49, 03 vs 378, 85 ± 38, 12. p < 0.01;), and systolic (−7, 17 ± 4, 67 mm/Hg. p < 0.001) and diastolic (−5, 48 ± 3, 92 mm/Hg. p < 0.001)blood pressure decreased only after antioxidant ice cream ingestion. No changes were found after control ice cream ingestion. Conclusions: For the first time, a natural antioxidant ice cream rich in polyphenols was demonstrated to acutely improve vascular function and decrease blood pressure in patients with metabolic syndrome through a reduction of oxidative stress and increase of NO bioavailability. This may be a novel valuable strategy for BP lowering in the high-normal range in which current hypertension management guidelines do not recommend drug treatment.